The Russian Financial Crisis and Workers' Remittances to Tajikistan and the Kyrgyz Republic - Sultonov, Mirzosaid (Journal of Reviews on Global Economics, 2016)
In this paper, we estimate the link between remittances and key macroeconomic variables of the host country (Russia) and the world's most remittance-dependent economies of Tajikistan and the Kyrgyz Republic. We mostly focus on the relationship during the ongoing Russian financial crisis. In particular, we estimate the responses of remittances to a shock in the exchange rate and per capita income in Russia and those of the key macroeconomic fundamentals of Tajikistan and the Kyrgyz Republic to a shock in remittance inflows. The empirical findings show that remittances serve as a channel to transfer the negative effects of the global and the Russian financial crises from the Russian macroeconomic fundamentals to the macroeconomic indicators of Tajikistan and the Kyrgyz Republic.